2017
DOI: 10.1250/ast.38.120
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the type and strength of emotion with music: An fMRI study

Abstract: In this paper, we used blood oxygenation level-dependent (BOLD) signals and emotion ratings to investigate the relationship between the type and strength of emotion induced by musical stimuli. Our goal was to establish a quantitative emotional evaluation method that uses brain activity. In Experiment 1, 26 participants rated 60 pieces of music using a semantic differential scale and 20 pieces were chosen on the basis of Russell's circumplex model. In Experiment 2, we investigated the relationships between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…We recorded the T1-weighted structural images (echo time [TE] = 4 ms, repetition time [TR] = 9.4 ms, flip angle = 8, field of view [FOV] = 256 × 256 mm, 192 slices, inversion time [TI] = 1013 ms, voxel size = 1 × 1 × 1 mm) and echo-planar whole-brain volumes (30 slices; TR = 3000 ms; TE: 50 ms; 4 mm thickness with a 1 mm gap; transverse; FOV: 192 × 192 mm; matrix size: 64 × 64; fractional anisotropy [FA]: 90°) as functional imaging data on a 1.5-tesla MRI scanner (Echelon Vega, Hitachi Medical, Chiba, Japan), according to a previously reported protocol ( Okuya et al. 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…We recorded the T1-weighted structural images (echo time [TE] = 4 ms, repetition time [TR] = 9.4 ms, flip angle = 8, field of view [FOV] = 256 × 256 mm, 192 slices, inversion time [TI] = 1013 ms, voxel size = 1 × 1 × 1 mm) and echo-planar whole-brain volumes (30 slices; TR = 3000 ms; TE: 50 ms; 4 mm thickness with a 1 mm gap; transverse; FOV: 192 × 192 mm; matrix size: 64 × 64; fractional anisotropy [FA]: 90°) as functional imaging data on a 1.5-tesla MRI scanner (Echelon Vega, Hitachi Medical, Chiba, Japan), according to a previously reported protocol ( Okuya et al. 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…However, many studies have simply explored how different emotions are processed, such as sadness, happiness, and fear (Bogert et al, 2016). For example, Okuya et al (2017) identified the left thalamus being heavily involved in responses to sad music. However, with consideration to our model of sad states, having one categorization of "sad" will not produce a comprehensive understanding of the neurological behavior in response to sad music.…”
Section: Future Directionsmentioning
confidence: 99%